Tinjauan Yuridis Dan Konseptual Terhadap Dituangkannya Substansi Perjanjian Atau Kontrak Ke Dalam Memorandum of Understanding (MoU) - Ni Nyoman Putri Purnama Santhi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
In principle, a agreement or contract is an effort to ensure legal protection with the principle of freedom of contract in conducting business transactions. In addition, there is also a memorandum of understanding (MOU) as another written legal form of the principle of freedom of contract. In practice, MOU are almost equated with contracts or agreements. However, if examined theoretically, the two are certainly different. This inaccuracy is often based substantially on pouring the substance of the contract into the MOU. On the other hand, an MOU is more appropriately understood as an agreement on basic matters between parties and only then should it be accompanied by a agreement or contract later. This causes confusion so that it is undeniable that it will have implications for losses for the parties. This research uses a normative method by examining laws and legal instrument, books, journals, and articles related to the discussion of MOU and agreements or contract. The results show that the MOU is not a contract and does not yet have binding force. Thus, it is necessary to discuss juridically and conceptually which will be presented in this research.